The mode of delivery and some selected obstetric factors as predictors of post-partum depression - Fatemeh Abdollahi; Azhar MD Zain (Babol University of Medical Sciences, 2015)
Background: The most prevalent mental or emotional problem associated with childbirth is post-partum depression (PPD). This study was designed to determine the psychological responses of Iranian women to difficult childbirth.  Methods: In this prospective cohort design, incidence rate and associated obstetric predictors of PPD over twelve week's post-partum were investigated among 1801 non depressed pregnant women attending primary health centers (PHCs) of Mazandaran province from January to June 2009 using the Iranian version of the Edinburgh Postnatal Depression Scale (EPDS > 12). Using logistic regression analyses, odds ratios (ORs) for the significant obstetric risk factors that were significantly associated with PPD from chi-square tests were calculated. The associations were controlled for possible socio-demographic confounding factors.  Results: The incidence proportions of depression occurring over a 12 weeks period of post-partum were 12.30%. The regression model showed that the risk of PPD was increased by experienced recurrent urinary infection [OR=2.25, (95% CI: 1.15-4.38), unwanted pregnancy [OR=1.97, (95% CI: 1.15-3.35)] and gestational diabetes [OR=3.41, (95% CI=1.46-5.88)] during pregnancy.  Conclusions: Although the mode of delivery was not predictive of PPD, other difficulties during pregnancy were associated with higher levels of depressive symptoms over 12 week's post-partum that needs on-time interventions.